ICT measures application of peculiarities in technology lessons - Lukšėnienė, Alina; Žygaitienė, Birutė; Pošiūnaitė, Kristina (Pedagogika, 2014)
Relevance.There have been performed a number of studies and international projects in the country, related to IT deployment and ICT skills education in schools: since year 2004, a “General computer literacy” research is carried out annually, a series of scientific, methodological, information works, reports have been produced to convey experience of the ICT implementation in education. The study was conducted to investigate how ICT education skills are organized in technology lessons. The aim of the researchis to analyze IT tools application peculiarities in the elementary school for 5–8 classes in the technology lessons. The objectives of the researche as follows: 1. To identify the importance of education for pupils’ ICT skills in the elementary school during technology lessons. 2. To investigate the aims of IT usage during educational process which are used by technology teachers. 3. To analyse the features of ICT application skills during technology lessons for 5–8 grade students. 4. Summarize the major problems associated with the application of IT in the technology lessons. The empirical method was applied in the research. The survey was carried out in 2011–2012 school year at Lithuanian general education schools. The data of all respondents was statistically treated (n = 603): managers of elementary school (n= 215), technology teachers (n= 112) and 5–8 grades students (n = 276). The study found that in order to develop pupils’ skills in information technology more attention should be paid to ensuring high-speed internet connection, the installation of computer individual sites, modern interactive teaching material, learning space development, educational content adaptation for work in cyberspace, for dissemination of good practice. It is also important to create conditions for students to develop consistently the ICT application skills through technology lessons in general education schools. In the educational content, IT dominate as a tool for reaching the lesson objectives, effectively exploiting the lesson time and space. The survey revealed that majority of teachers plan the use of ICT in lessons and always include it in the annual work plans. Most of the teachers use IT in extracurricular activities. Technology teachers use IT often and have used almost the same amount of all programs during classes. The study revealed that the most popular and most commonly used are the search, preparation of presentations and text editing programs. According to technology teachers opinion, usage of IT improves students’ information and technical skills and partly develops students critical thinking, learning, creativity and communication skills. Students of 5–8 grades expressed the opinion that, usage of IT during technology lessons mostly develops information and technological skills, partly promotes thinking and collaboration as well. However, unlike the technology teachers, almost half of the students think that the use of IT tools do not promote learning motivation. School principles and teachers felt that the application of IT for students of 5–8 grades during technology lessons more interestingly conveys the educational content, the work with the latest software; hardware encourages the teachers to improve themselves as well. Technology teachers faces with some problems by applying IT during their lessons: one-third of the participating teachers’ lack of licensed programs and computer access. More than half of the teachers do not have internet access in their classrooms. Even two-thirds of the teachers would like to improve their computer literacy. Almost a third of teacher’s state that school schedules are not aligned. And only the tenth of teachers involved in the study says that do not feel the lack of computers and licensed programs.